2019
DOI: 10.3390/v11090845
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up of Viral Parameters in FeLV- or FIV-Naturally Infected Cats Treated Orally with Low Doses of Human Interferon Alpha

Abstract: Specific treatments for the long-life infections by feline leukemia virus (FeLV) and feline immunodeficiency virus (FIV) are either toxic, expensive or not too effective. Interferon α (IFN-α) is an immunomodulatory molecule which has been shown in vitro to decrease the release of infective particles. The aim of this study was to follow the progress of the clinical score and viral parameters of FeLV- and FIV-naturally infected privately owned cats treated with recombinant human IFN-α (rHuIFN-α, Roferon-A). Twen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…In this study, we followed-up the disease in each cat by comparison to M0, before the start of the treatment. This approach has been followed by other researchers when studying naturally infected cats [20,[25][26][27][28], who have suggested that values at M0 are potentially more representative than a placebo in studies in field conditions with animals in unknown and probably different stages of infection. In addition, a placebo-treated or non-treated group of cats would have been ethically controversial, as owners demand a therapeutic option for their cats.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, we followed-up the disease in each cat by comparison to M0, before the start of the treatment. This approach has been followed by other researchers when studying naturally infected cats [20,[25][26][27][28], who have suggested that values at M0 are potentially more representative than a placebo in studies in field conditions with animals in unknown and probably different stages of infection. In addition, a placebo-treated or non-treated group of cats would have been ethically controversial, as owners demand a therapeutic option for their cats.…”
Section: Discussionmentioning
confidence: 99%
“…Animal handling, treatment, reagent manipulation, and data collection were all carried out in compliance with guidelines for Good Clinical Practice, and Good Laboratory Practice of the Animal Welfare Committee of the Veterinary Clinical Hospital and the Complutense University, and the experimental procedures were approved by the Institutional Animal Care and Use Committee of the Complutense University [20].…”
Section: Animals and Treatmentmentioning
confidence: 99%
See 3 more Smart Citations